Peningkatan Pengetahuan Dalam Penyelenggaraan Elektronik Rekam Medis Di Rumah Sakit - Nannyk Widyaningrum; Winda Azmi Meisari; Viviana Rahmawati (Nusantara Mengabdi Kepada Negeri, 2024)
Electronic Medical Records as a form of renewal of health services, which has emerged as a response to and challenges arising from advances in technology. The Minister of Health Regulation No. 269/Menkes concerning Medical Records is no longer in accordance with developments in science and technology, health service needs and the legal needs of society. At this time the government has determined the regulations to be used, namely Minister of Health Regulation no. 24 of 2022 concerning Medical Records. With this regulation, hospitals must improve their preparation so that they can be integrated with the government system. The aim of this PKM is to increase the knowledge of medical personnel in administering electronic medical records in hospitals. The PKM implementation method includes material presentation, discussion and evaluation. The target of PKM consists of 14 health workers with the results of PKM being an increase in health workers' knowledge in maintaining medical records.